Photodynamic effect of TPP encapsulated in polystyrene nanoparticles toward multi-resistant pathogenic bacterial strains: AFM evaluation - Malá, Zuzana; Žárská, Ludmila; Malina, Lukáš; Langová, Kateřina; Večeřová, Renata; Kolář, Milan; Henke, Petr; Mosinger, Jiří; Kolářová, Hana (Scientific reports, 2021)
Photodynamic inactivation (PDI) is a promising approach for the efficient killing of pathogenic microbes. In this study, the photodynamic effect of sulfonated polystyrene nanoparticles with encapsulated hydrophobic 5,10,15,20-tetraphenylporphyrin (TPP-NP) photosensitizers on Gram-positive (including multi-resistant) and Gram-negative bacterial strains was investigated. The cell viability was determined by the colony forming unit method. The results showed no dark cytotoxicity but high phototoxicity within the tested conditions. Gram-positive bacteria were more sensitive to TPP-NPs than Gram-negative bacteria. Atomic force microscopy was used to detect changes in the morphological properties of bacteria before and after the PDI treatment.
Keywords: příprava léků; polystyreny; mikroskopie atomárních sil; Photochemical Processes; Photochemotherapy; porfyriny; Nanoparticles; Bacteria; Drug Compounding; Porphyrins; Polystyrenes; fotochemoterapie; Microscopy, Atomic Force; nanočástice; fotochemické procesy